PENGARUH HAMBATAN INTERNAL TERHADAP DAYA OUTPUT ELEMEN TERMOELEKTRIK GENERATOR TIPE 10W-4V-40s - Eri Wiyadi; Lazuardi Umar (Komunikasi Fisika Indonesia, 2018)
Thermoelectric generator Type 10W-4V-40s powered by Seebeck effect by utilizing temperature difference in both sides of the element. The hot side (Th) of a TEG element is placed on a stand made of Aluminum-Dural material and given a heat source derived from a heater, on the cold side (Tc) TEG element installed heatsink to reduce heat energy through the cold side and keep the temperature low. The measurement of output power (PL) is done by variation of RL from 0 Ω to 20 Ω under temperature difference conditions (ΔT) varies with constant Tc at 30ºC, the result of the research indicates that the output power (PL) of the thermoelectric element is maximum at RL = 1 Ω when the minimum load decreases and is proportional to the increase in RL resistance. The internal resistance value (Rint) of the TEG element increases in proportion to the magnitude of ΔT on both sides of the element, on Tc and Th at room temperature (30ºC) the value of Rint is 0.85 Ω and the maximum value at ΔT = 50ºC is 1,043 Ω. This indicates that the TEG element depends not only on ΔT on both sides of the module, but also depends on the amount of temperature range used.